THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1944)
Abstract The article discusses the social significance of accounting and the public-interest aspect of public accounting. The author views the concept of accounting as a factor in social control. Too few men come from college with any appreciation of the relation between the accounting principles and practices which they have studied and the social consequences that may result from their application. Regulatory bodies in recent years have taken it upon themselves to determine accounting principles and practices in many cases in order to promulgate their regulatory objectives without making their social consequences clear. The question can be fairly raised as to whether the profession and the teachers have made the contribution that should be made in relating accounting policies in use to such consequences. Any consideration as to the soundness of a particular accounting policy is sterile which does not embrace the possible social consequences thereof. The theory apparently underlying the typical program in business or accounting reflects a belief that education for living and education for working can be successfully integrated throughout the four years leading to a bachelor's degree, or the five years to a master's degree. This expresses the idea that working is a part of living and living involves working.